แนวทางการจัดการพื้นที่เกษตรกรรมในเขตเทศบาลนครเชียงราย จังหวัดเชียงราย - ไพศาล ขจรวุฒินันทชัย (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The research of management approach of agricultural area in Chiang Rai municipality, Chiang Rai province aimed to 1) Understand the agricultural context in Chiang Rai municipality 2) Study people’s attitude towards in lands in Chiang Rai municipality 3) Pride the support information and possible way to manage appropriate agricultural lands in Chiang Rai municipality. Data was collected by focus group discussion from key stakeholders such as village, headman, agricultural group leader and questionnaire interviewed related officer of Chiang Rai municipality. Moreover, questionnaire was employed and specific randomly selected 60 peoples to interviewed from 3 study areas is Chiang Rai municipality stadium, Chiang Rai beach park and Nong Pueng. Data analysis was applied both qualitative and quantitative methods with explained by frequent, percentage, maximum, minimum and average. Currently, Chiang Rai city is rapidly expanding. The main factors caused by the rapid increase of population, migration and work migration. These facts ware affected to agricultural land and quality of life of Chiang Rai people, and intend to occur respectively. Chiang Rai municipality is currently in the process of city planning in order to decrease city expansion to make a compact city and increases green area in the city. The area nearby Chiang Rai municipality stadium is closed to Kok river in many parts which the Kok river looks like river bend shape with beautiful scenery which should be the tourist attraction or hold the agricultural activities. Chiang Rai municipality stadium area is shady and also a relax place for people, only lack of development and promotion to be a real organic agricultural garden. Nong pueng area is a beautiful natural water source and could be developed to be an agricultural area. Previously, there were a lot of institutes educated and developed the area to be proper with the cooperation of people in the area but still lack of continuously managing. Result from interview found that majority of people viewed that agricultural area was not enough for agricultural practices with 86.7 percent. Management for agricultural area was still not enough for the needs of people in study areas at the percentage of 80. The impact for utilizing of agricultural area for other uses, majority of respondents viewed that it was impacts to agricultural area and there was not enough agricultural area for production at the percentage of 88.3. Although, these decreasing of agricultural area does not affected to people’s life but Chiang Rai municipality should also take immediate action plan for utilizing the proper with the cooperation with people in area for the utmost benefits of people in the area.